Synthesis and identifying the active site of Cu2Se@CoSe nano-composite for enhanced electrocatalytic oxygen evolution. (10th October 2019) - Wang, Xueyuan; Zhou, Yan; Tuo, Yongxiao; Lin, Yan; Yan, Youguo; Chen, Chen; Li, Yanpeng; Zhang, Jun
Abstract: The urgent demand for clean energy sources has led the oxygen evolution reaction (OER) became one of the most essential reaction due to its "rate-determining" nature for electrolysis of water. In this paper, a nano-composite of Cu2 Se@CoSe was synthesized using a colloidal method. This synthetic approach was capable for the synthesis of Cu2 Se, CoSe and Cu2 Se@CoSe. The nano-composite of Cu2 Se@CoSe exhibited electrocatalytic OER activity, with low overpotential of 251 mV at 10 mA cm −2 and 320 mV at 100 mA cm −2, and even beat the RuO2 at high current density ( i.e. > 80 mA cm −2 ). Long-term electrolysis test revealed the chemical and electrochemical stability over 20 h at high current density (150 mA cm −2 ). Furthermore, post-electrolysis experimental analyses indicated that CoOOH/Cu(OH)2 on Cu2 Se@CoSe played an important role in OER electrocatalysis, and they were readily oxidized from Cu + in Cu2 Se and Co 2+ in CoSe before the onset potential of OH − oxidation. The CoOOH/Cu(OH)2 served as both catalytic material and protective layer of Cu2 Se@CoSe, thus leading to enhanced OER catalytic activity and stability. It is believed that Cu2 Se@CoSe can be a potential candidate for fabricating sustainable OER electrocatalytic electrode.